Synthesis of Diamond Thin Film on Si Substrate by Microwave-Plasma CVD - CHEN, Chia-Fu; HOSOMI, Satoru; HUANG, Yen C (Journal of the Metal Finishing Society of Japan, 1988)
Diamond film was deposited by microwave plasma CVD from a CH4-H2 reactant gas at a subatmospheric pressure of 3.0kPa, in order to investigate the effects of such parameters as gas composition and flow rate on the growth rate and properties of the film. The silicon substrate, when polished with 5μm diamond paste, was observed to have a favorable affect on film deposition. Growth rate reached a maximum of approx. 1μm/hr at 3% CH4, at<3% CH4 the growth rate was essentially dependent on the flow rate, while at>3% CH4, the rate decreased with an increasing flow rate. The films exhibited an agglomerate structure of idiomorphic grains when deposited at low CH4 levels, and consisted of agglomerates of increasingly round fine crystals when deposited at higher levels. The deposition rate was essentially constant over the whole reaction time. The highest film deposition rate was obtained at a microwave power of 220W, whereby the substrate was, estimated to reach a temperature of 1173K.